The Types of Discourse Markers in Joko Widodo’s Speeches in KTT APEC China in 2015 - Syahbuddin - Nasution; Busmin - Gurning; I Wayan Dirgeyasa Tangkas (Universitas Negeri Medan, 2020)
This study deals with the discourse marker in Joko Widodo’s Speeches in KTT APEC CHINA in 2015. This study attampted to investigate the domaint elements of Discourse Marker of Joko Widodo speeches in KTT APEC in CHINA 2015, the type and how discourse marker are coded in the president Joko Widodo specches in KTT APEC in CHINA 2015. The study was conducted by quantitative design. The data in this study were the vidio of JOKO widodo’s Speeches in KTT APEC in China 2015 which got 102 clauses from the vidio. The clauses were transcribed in order to be analyzed. In relation to the problems of the study, the purpose of the study is to find the types of discourse markers and to elaborate the reasons of occurrence of discourse markers used the speech based on situational context. And this research was using descriptive qualitative method. From the data analysis and findings, there were four categories from discourse markers found in Joko Widodo speeches they are interpersonal category, referential categories, structural category and cognitive category, and the dominant category found was cognitive category.Keywords: Discourse Markers, Speeches and Types, KTT APEC